(untitled) (International Conference on Education, Psychology and Humanities, 2026)
This thesis examines the pedagogical conditions necessary for developing students’ civic consciousness in the digital information environment. In modern higher education, students encounter large volumes of information through social networks, digital platforms, online media, electronic educational resources and interactive communication spaces. These conditions influence their worldview, social attitudes, legal awareness and civic behavior. Therefore, the development of civic consciousness requires not only traditional educational methods, but also purposeful pedagogical work with digital content, media literacy, critical thinking and responsible online communication. The thesis argues that civic consciousness can be effectively developed when higher education institutions create an educational environment based on information culture, ethical digital behavior, reflective learning, social participation and value-oriented media analysis.